Links between eastern equatorial Pacific stratification and atmospheric CO2 rise during the last deglaciation. (5th November 2015) - Bova, Samantha C.; Herbert, Timothy; Rosenthal, Yair; Kalansky, Julie; Altabet, Mark; Chazen, Caitlin; Mojarro, Angel; Zech, Jana
Abstract: It is difficult to untangle the mixed influences of high‐ and low‐latitude climate forcing in the eastern equatorial Pacific (EEP). Here we test the hypothesis that the Southern Ocean drove change in the EEP via subsurface intermediate waters during the last deglaciation. We use the δ 18 O signature of benthic foraminifera to reconstruct water density changes during the last 25 kyr at three intermediate water depths (370 m, 600 m, and 1000 m) in the EEP. Carbonate δ 18 O records a combined signature of temperature and salinity and is therefore more closely related to density than temperature or salinity alone. We find that benthic foraminiferal δ 18 O values decreased first in the subsurface, simultaneously with rising temperatures over Antarctica, and propagated up to the surface within ~3 kyr. The early subsurface response initiated a rapid decrease in density stratification over the upper water column as indicated by reduced δ 18 O gradients between surface and intermediate depths. Stratification of the upper water column remained low through the termination, with stratification minima reached during Heinrich Stadial 1 and the Younger Dryas (YD), synchronous with the two‐part deglacial rise in atmospheric CO2 . Centennial‐scale shifts toward heavier δ 18 O signatures at 370 and 600 m during the YD indicate short‐lived shifts in the Subantarctic Mode Water/Antarctic Intermediate Water boundary to shallower intermediate depths. We suggest that decreased density gradients during the deglaciation accelerated vertical mixing across the EEP, and potentially the entire South Pacific subtropical gyre, which enhanced CO2 delivery from depth to the surface ocean and atmosphere. Key Points: EEP intermediate waters responded to SH climate during the last deglaciation Early warming in the EEP subsurface altered upper water column stratification Weak stratification during the YD and HS1 led to enhanced CO2 degassing